ECG from basics to essentials : step by step - Stroobandt, R. (Roland); Barold, S. Serge; Sinnaeve, Alfons F. (Chichester, West Sussex, UK ; Hoboken, NJ : Wiley Blackwell, 2015)
This brand new guide assists students, interns and residents in developing a functional understanding of the set-up, workings and interpretation of ECGs -Step-by-step graphics and short, bite-sized explanations -Covers all major cardiac abnormalities including hypertrophy, arrhythmias, conduction blocks, and pre-excitation syndromes -Begins with a section on physiology of the heart and the basic set up of ECG recording -Features top tips on what to look for, complete with illustrated examples -Supported by a companion website featuring additional practice tracings.
Anatomy and basic physiology -- ECG recording and ECG leads -- The normal ECG and the frontal plane QRS axis -- The components of the ECG waves and intervals -- P waves and atrial abnormalities -- Chamber enlargement and hypertrophy -- Intraventricular conduction defects -- Coronary artery disease and acute coronary syndromes -- Acute pericarditis -- The ECG in extracardiac disease -- Sinus node dysfunction -- Premature ventricular complexes (PVC) -- Atrioventricular block -- Atrial rhythm disorders -- Ventricular tachycardias -- Ventricular fibrillation and ventricular flutter -- Preexcitation and Wolff-Parkinson-White syndrome (WPW) -- Electrolyte abnormalities -- Electrophysiologic concepts -- Antiarrhythmic drugs -- Pacemakers and their ECGs -- Errors in electrocardiography monitoring, computerized ECG, other sites of ECG recording -- How to read an ECG.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Electrocardiography -- Methods; Cardiovascular diseases -- Diagnosis; Electrocardiography -- instrumentation; Electrocardiography -- Methods; Cardiovascular system -- Diseases -- Diagnosis; Electrocardiography; Medical; Electronic books